Classifying and diagnosing systemic lupus erythematosus in the 21st century - Aringer, Martin (Rheumatology (Oxford), 2020)
The EULAR/ACR 2019 classification criteria for SLE constitute a current and optimized clinical approach to SLE classification. Classification is still not based on molecular approaches and the results from large studies using polyomics may be interpreted as demonstrating the relevance of the genetic and environmental background rather than splitting SLE into several entities. In fact, an association study within the EULAR/ACR classification criteria project found associations between manifestations only within organ domains. This independency of various organ manifestations argues for SLE as one disease entity. The current review article will therefore concentrate on the clinical and immunological manifestations of SLE and on what we have already learned in this century. Moreover, the structure and essential rules of the EULAR/ACR 2019 classification criteria will be discussed. While classification and diagnosis are distinct concepts, which have to remain clearly separated, information derived from the process towards the classification criteria is also useful for diagnostic purposes. Therefore this article also tries to delineate what classification can teach us for diagnosis, covering a wide variety of SLE manifestations.